Paraneoplastic and Other Autoimmune Encephalitides: Antineuronal Antibodies, T Lymphocytes, and Questions of Pathogenesis - Greenlee, John E.; Carlson, Noel G.; Abbatemarco, Justin R.; Herdlevær, Ida; Clardy, Stacey L.; Vedeler, Christian A. (Frontiers in Neurology, 2022)
Autoimmune encephalitides associated with antineuronal antibodies, including conditions found in patients with underlying cancer and paraneoplastic disorders, represent an increasingly recognized cause of devastating neurological disease and also an emerging area of illness associated with immune checkpoint inhibitors. Two groups of antibodies may be detected in affected patients: antibodies directed against neuronal cell surface membrane receptor or other proteins, and antibodies directed against intracellular antigens located in neuronal cytoplasm or nuclei. The first group includes antibodies against the N-methyl-D-aspartate receptor (NMDAR), associated with autoimmune encephalitis in patients of all ages, and antibodies to the Leucine-rich glioma-inactivated 1 protein, found in patients with faciobrachial dystonic seizures and limbic encephalitis. The conditions associated with these antibodies are, in aggregate, more common than viral encephalitides and are often amenable to treatment. The second group includes antibodies such as anti-Yo antibody, found in patients with paraneoplastic cerebellar degeneration and anti-Hu antibody, associated with paraneoplastic encephalomyelitis. These antibodies are characteristically found in patients with underlying cancer: their associated syndromes may antedate tumor diagnosis, and the conditions themselves are notoriously difficult to treat. Within the last few years, major advances have been made in understanding the neurological disorders associated with anti-NMDAR and other antibodies against neuronal cell surface membrane antigens, both in humans and in animal models. In contrast, the events which lead to neuronal death in conditions associated anti-Yo, anti-Hu or similar antibodies to intracellular neuronal antigens remain poorly understood. Although tissue culture studies suggest a direct pathogenic role for these antibodies, the relative roles of antibodies and T lymphocytes have not been defined in an animal model. In this review we discuss current knowledge of these two groups of in terms of their discovery, how they arise, the interaction of both types of antibodies on their molecular targets, and the attempts which have been made to reproduce human neuronal injury in tissue culture models and experimental animals. We then discuss the emerging area of syndromes of autoimmune neuronal injury associated with immune checkpoint inhibitors, and the implications of current research in terms of treatment of affected patients.